Revolutionary suicide and other desperate measures narratives of youth and violence from Japan and the United States - Hurley, Adrienne Carey 1968- (Duke University Press, 2011)
Survivor discourse, the limits of objectivity, and Orpha -- Shizuko, the silent girl : Uchida Shungiku's Fazaa Fakkaa -- "Mama, he treats your daughter mean?" : Dorothy Allison's Bastard out of Carolina -- Engendering first world fears : the teenager and the terrorist -- "Killer kids" and "cutters" -- The fiction of Hoshino Tomoyuki and Japanarchy 2k : lonely hearts revolution -- Conclusion : a case for reparations
Description based on print version record. - Includes bibliographical references and index
Keywords: Youth and violence / Japan; Youth and violence / United States; Kindesmisshandlung; Aggression; Jugend; Japan; USA